2015
DOI: 10.1007/s12032-015-0483-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome expression profiling in chewing-tobacco-associated oral cancers: a pilot study

Abstract: The current study was undertaken with a view to identify differential biomarkers in chewing-tobacco-associated oral cancer tissues in patients of Indian ethnicity. The gene expression profile was analyzed in oral cancer tissues as compared to clinically normal oral buccal mucosa. We examined 30 oral cancer tissues and 27 normal oral tissues with 16 paired samples from contralateral site of the patient and 14 unpaired samples from different oral cancer patients, for whole genome expression using high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Smoking is one of the crucial risk factors for OSCC [31, 33]. In a pilot study, whole genome expression profiling of Indian patients with tobacco chewing-associated oral cancers implicated that WISP1 is one of the representative apoptosis-related deregulated genes in oral cancer [34]. Chen et al revealed that WISP1 was overexpressed in non–small cell lung carcinoma (NSCLC) samples compared with their normal lung tissue counterparts, implicating that WISP1 might act as an oncoprotein in NSCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is one of the crucial risk factors for OSCC [31, 33]. In a pilot study, whole genome expression profiling of Indian patients with tobacco chewing-associated oral cancers implicated that WISP1 is one of the representative apoptosis-related deregulated genes in oral cancer [34]. Chen et al revealed that WISP1 was overexpressed in non–small cell lung carcinoma (NSCLC) samples compared with their normal lung tissue counterparts, implicating that WISP1 might act as an oncoprotein in NSCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…A study that analyzed expression of AIM2 protein in colon cancer tissue microarray (TMA) [29] or studies that analyzed AIM2 mRNA levels in colorectal [29,30] and prostate [20] cancer specimen indicated that reduced or loss of AIM2 expression in cells is associated with cancer development and its progression to an advanced stage. However, increased levels of the AIM2 mRNA and protein have been reported in a number of inflammation and virus-associated cancers [31][32][33][34][35][36]. Therefore, given that AIM2 expression is also increased in senescent cells [19], further work will be needed to determine whether cancer therapy-induced accumulation of senescent cells in tumors contributes to the observed increased levels of AIM2 mRNA or protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in lung cancer tissues, high-grade ADC expressed more inflammasome components and products than low-grade ADC [33]. Similarly, in chewing-tobacco-associated oral cancer tissues, AIM2 mRNA levels were higher than clinically normal oral buccal mucosa [34].…”
Section: Increased Expression Of Aim2 In Certain Virusassociated and mentioning
confidence: 91%
See 1 more Smart Citation
“…35,36 In comparison, few studies discuss the impact of chewing or other forms of smokeless tobacco on gene expression using high-throughput techniques. [37][38][39] Our group has previously reported the proteome-wide alterations in oral keratinocytes upon chronic exposure to smokeless tobacco and identified stearoyl CoA desaturase as a potential therapeutic target in head and neck squamous cell carcinoma. 40 Metabolic differences have been reported between smokers and snuff users but the molecular/proteomic alterations between smokers and tobacco chewers are not well elucidated.…”
Section: Introductionmentioning
confidence: 99%